Hypsarrhythmia in epileptic spasms: Synchrony in chaos. (May 2018) - Nenadovic, Vera; Whitney, Robyn; Boulet, Jason; Cortez, Miguel A.
Highlights: Phase synchrony analysis supports the visual inspection of hypsarrhythmia. Hypsarrhythmia appears more synchronized than the electrodecremental event. Phase synchrony and its variability is a novel computational tool for hypsarrhythmia. Abstract: Purpose: Hypsarrhythmia is an electroencephalographic pattern associated with epileptic spasms and West syndrome. West syndrome is a devastating epileptic encephalopathy, originating in infancy. Hypsarrhythmia has been deemed to be the interictal brain activity, while the electrodecremental event associated with the spasms is denoted as the ictal event. Though characterized as chaotic, asynchronous and disorganized based on visual inspection of the EEG, little is known of the dynamics of hypsarrhythmia and how it impacts the developmental arrest of these infants. Methods: As an exploratory and feasibility study, we explored the dynamics of both hypsarrhythmia and electrodecremental events with EEG phase synchronization methods, and in a convenience sample of three outpatients with epileptic spasms. As ictal events are associated with prolonged phase synchronization, we hypothesized that if hypsarrhythmia was indeed the interictal brain activity that it would have lower phase synchronization than the electrodecremental event (ictal phase). Results: We calculated both the phase synchronization index and the temporal variability of the index in three patients with infantile spasms. Two patients had hypsarrhythmia and electrodecremental events and one had hemi-hypsarrhythmia. We found that the hypsarrhythmia pattern was a more synchronized state than the electrodecremental event. Conclusions: We have observed that the hypsarrhythmia pattern may represent a more synchronized state than the electrodecremental event in infants with epileptic spasms. However, larger studies are needed to replicate and validate these findings. Additionally, further inquiry is required to determine the impact that increased synchronization may have on developmental outcomes in infants with epileptic spasms.